Managing Digital Library Services to Increase Access to Information - Amin Yusdian Faishol; Dani Rustani; Sherinda Wibowo Putri; Siti Aisah; Irpan Taufik Hidayat (Communigate, 2025)
Along with the development of time and technology, currently library services have transformed and adapted to technology, one of the transformations is digital libraries. Digital libraries allow users to access various information sources anytime, anywhere, without time and location restrictions. The research method used in this research is a literature study method, this method is carried out by examining various literature studies needed in the research, data collection techniques using data such as journals, books, and web references. The results of this study reveal, to achieve effective management of digital library services can implement several things, namely: 1) Digital Collection Management, 2) Use of information management systems, 3) Interactive services for users. Then, the factors that support the success of digital library management include, reliable technology infrastructure, quality content and according to user needs, accessibility and easy-to-use interfaces, cooperation with other institutions such as universities or research institutions, and regular assessment and feedback to improve service quality. The impacts of digital library management on information access are: 1) Easier access to information, 2) Availability of Richer Materials, 3) Ease of Searching or Sorting, 4) Cooperation and interaction.